Предмет: Алгебра,
автор: milka50
упростить и подставить
Приложения:
Ответы
Автор ответа:
0
36ав-(3а+6в)² = 36ав - (9а²+36ав+36в²) = 36ав - 9а² -36ав - 36в² =
= -9а²-36в² при а= √3 при в=√6
-9 (√3)² - 36 (√6)² = -9*3 - 36*6 = -27 - 216 = -243
= -9а²-36в² при а= √3 при в=√6
-9 (√3)² - 36 (√6)² = -9*3 - 36*6 = -27 - 216 = -243
Похожие вопросы
Предмет: Алгебра,
автор: alksandrtutikov
Предмет: История,
автор: tvboxuser32tv
Предмет: Математика,
автор: ebanutiy123
Предмет: История,
автор: musulmanka20001
Предмет: Математика,
автор: Кирилл5625